IMPACT OF NURSE-ASSISTED CARDIAC REHABILITATION INTERVENTIONS ON HEALTH BEHAVIOR MODIFICATION OF PATIENTS WITH MYOCARDIAL INFARCTION - Sidra Bibi; Sarfraz Masih; Muhmmad Afzal (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: The rate of coronary thrombosis, especially MI, is increasing in Pakistan day by day and cardiologists are using interventional technology like angioplasty to treat such diseases. But this treatment is not enough for the patients to remain healthy for a long time and to get back to their daily life activities. Cardiac Rehabilitation is now becoming an utmost requirement for the cardiac patients due to their needs of health behaviors modifications to increase their expected year of life, which is fulfilled by the collaboration of a cardiologist, nurse, physiotherapist and nutritionist. Study design: Quasi experimental (pre and post) Setting: The Lahore School of Nursing, UOL. Methodology: The study employed Paired sample T-tests and descriptive statistics to examine changes in variables before and after cardiac rehabilitation. Results: There was a significant improvement in patients’ overall health behavior pre- to post-CR, Results showed a significant positive correlation between post-CR behaviour and physical activity (r = 0.566; P = 0.000), food intake(r = 0.316; P = 0.001), and medication adherence (r = 0.428; P = 0.000). Conclusion(s): pre interventions data were obtained from MI patients there were not any noteworthy practice in physical activity, nutrition and medication adherence. By the conclusion of the interventions, however, we had seen statistically significant changes in all three aspects of health behaviors.